PENELUSURAN POTENSI ARKEOLOGIS DI KAWASAN KARST GOMBONG SELATAN - . Anggraeni (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
The archaeological value of Gombong region, especially for the karsts area, has never been recognized before. In contrast, a long term research project done in the karsts area of Pegunungan Seribu, 60 km to the east of Gombong, has recovered a huge amount of archaeological data. By conducting surface surveys focused on caves followed by observation on cave morphology and analysis of surface finds, the archaeological value of the karsts area of Gombong can be acknowledged. The result is, two of seven caves observed have positive indications of habitation. Similarity between type and technology of stone and bone artifacts of Gombong with the compared area can be seen in some degree. So, as can be proved by the existence of stone and bone artifacts in Jatijajar and Banteng caves, it can be concluded that the artifact productions and technology of both areas were at the same level as those at Pegunungan Seribu.